2013
DOI: 10.1021/jz3021155
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Trends in the Electrocatalytic Activity of Metals and Enzymes for CO2 Reduction to CO

Abstract: We develop a model based on density functional theory calculations to describe trends in catalytic activity for CO2 electroreduction to CO in terms of the adsorption energy of the reaction intermediates, CO and COOH. The model is applied to metal surfaces as well as the active site in the CODH enzymes and shows that the strong scaling between adsorbed CO and adsorbed COOH on metal surfaces is responsible for the persistent overpotential. The active site of the CODH enzyme is not subject to these scaling relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
685
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 681 publications
(716 citation statements)
references
References 30 publications
26
685
1
4
Order By: Relevance
“…Similar studies can be found in the literature in which the effects of different enzyme types having different metal active centers and the contribution of those metals to the formation of CO and formate were investigated 76, 77. Nørskov and co‐workers reported a good overiew of the design parameters for enzymatic catalysts using DFT calculations.…”
Section: Homogeneous Electrocatalysis For Co2 Reductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Similar studies can be found in the literature in which the effects of different enzyme types having different metal active centers and the contribution of those metals to the formation of CO and formate were investigated 76, 77. Nørskov and co‐workers reported a good overiew of the design parameters for enzymatic catalysts using DFT calculations.…”
Section: Homogeneous Electrocatalysis For Co2 Reductionsupporting
confidence: 65%
“…One of the important points noted in their paper is the ability of the metal center to bind CO and HCOO − while stabilizing oxygen in the latter. They also suggest that readers use noble metal centers in enzymes as such metals have rather high overpotentials for H 2 formation 76. In their review, Mondal et al.…”
Section: Homogeneous Electrocatalysis For Co2 Reductionmentioning
confidence: 99%
“…Nørskov and co‐workers used density functional theory (DFT) calculations to describe trends in catalytic activity for CO 2 reduction to CO as a function of the adsorption energies of the two reaction intermediates—COOH and CO 46. They revealed that on Au and Ag, the reaction rate was limited by CO 2 activation, and resultant CO desorbed easily from their surfaces; whereas on Pd, Ni, Pt, and Rh, CO 2 activation and conversion to adsorbed CO was facile, and the reaction rate was mainly limited by the desorption of CO due to its strong affinity.…”
Section: Electrocatalytic Materials For Co2 Reductionmentioning
confidence: 99%
“…Meanwhile such large negative potential would also trigger the evolution of H 2 since the half reaction potential to form H 2 is 0 V. The sluggish in overpotential is chiefly caused by the multi‐step processes of reduction, density function theory (DFT) studies suggests the mechanism include the following steps69, 70, 71, 72:CO2+*+normalH+(aq)+normaleCOOH* COOH*+normalH+(aq)+normaleCO*+normalH2O(l) CO*CO(g)+*where * denotes a free active site. From these elementary reactions, we can intuitively conclude that materials which could both stabilize COOH* and destabilize CO* would be a prominent catalyst for reduction of CO 2 to CO.…”
Section: Edges As Active Sitesmentioning
confidence: 99%